Sistem Pakar Diagnosa Kerusakan Mesin Jahit Janome Menggunakan Metode Variable Centered Intelligent Rule System (VCIRS) dan Naïve Bayes - Aprisa Sianturi (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2021)
The Janome sewing machine is one of the portable machine products that can be used for sewing and embroidery clothes with maximum results, but the number of technicians who are experts or experts in diagnosing damage to Janome sewing machines is currently still low. Therefore, researchers designed a system that can be used to help experts or experts diagnose the damage that occurred to a Janome sewing machine using Microsoft Visual Studio 2008. This system is designed as an expert or expert can diagnose the damage that occurs to a Janome sewing machine based on symptoms. the symptoms on the machine. The methods applied to this system are the Variable Centered Intelligent Rule System (VCIRS) and the Naïve Bayes method. The results of this study resulted in an expert system that can diagnose the Janome sewing machine malfunction to operate on a personal computer.